(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Extreme Programming (XP) has been called one of the most successful methods in software development. XP comprises a set of practices designed to work together to provide value to the customer. During the XP lifecycle, developers and customers regularly encounter situations in which they need to make decisions or evaluate factors. This affects the development process and team productivity. We propose to use the Analytic Hierarchy Process (AHP) as a means to systematize and streamline the decision process. AHP eliminates conflict because it elaborates input from every member of the team. Thus, the adoption of AHP can help accomplish XP values and fulfill team needs. This paper presents an example of applying the AHP to decide which testing technique to adopt depending on a series of project-specific parameters.